2020
DOI: 10.1016/j.mbplus.2020.100031
|View full text |Cite
|
Sign up to set email alerts
|

Salicylate suppresses the oncogenic hyaluronan network in metastatic breast cancer cells

Abstract: The oncogenic role of hyaluronan in several aspects of tumor biology has been well established. Recent studies by us and others suggest that inhibition of hyaluronan synthesis could represent an emerging therapeutic approach with significant clinical relevance in controlling different breast cancer subtypes, including triple-negative breast cancer. Epidemiological and preclinical studies have revealed the therapeutic potential of aspirin (acetyl salicylate), a classical anti-inflammatory drug, in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 73 publications
0
10
0
1
Order By: Relevance
“…Low metastatic MCF-7 (ER+) and highly metastatic MDA-MB-231 and Hs 578T (triple negative, ER-/PR-/HER2-) breast cancer cell lines (obtained from the ATCC) were utilized in the present study. For cell cultures, complete media (DMEM, #LM-D1109/500, Biosera) containing 10% fetal bovine serum and antimicrobial agents cocktail were used as described before ( 29 ). All chemicals were of the best commercially available grade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low metastatic MCF-7 (ER+) and highly metastatic MDA-MB-231 and Hs 578T (triple negative, ER-/PR-/HER2-) breast cancer cell lines (obtained from the ATCC) were utilized in the present study. For cell cultures, complete media (DMEM, #LM-D1109/500, Biosera) containing 10% fetal bovine serum and antimicrobial agents cocktail were used as described before ( 29 ). All chemicals were of the best commercially available grade.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate cell viability, control and DBD-CAP-treated cells were stained with crystal violet solution followed by optical density measurement at 570 nm as described before ( 29 ). As an alternative method, breast cancer cells (control and DBD-CAP-treated cells cultured for 24 h) were detached from the 35-mm dishes with trypsin-EDTA 1× in PBS for 3 min, collected and counted on a hemocytometer counting chamber according to standard protocols.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, a recent paper reports that the activation of AMPK by salicylate affects the expression levels of HASes as well as the deposition of secreted and cell-associated HA, probably affecting HAS2 phosphorylation or salicylate glucuronidation and therefore, altering the availability of UDP-GlcUA. 97…”
Section: Role Of Ampk In Ha Metabolism and Cell Homeostasismentioning
confidence: 99%
“…Salicylic acids and derivatives are mostly used in antipyretic, analgesic and anti-inflammatory in clinical practice and belong to non-steroidal anti-inflammatory drugs. It also has a certain therapeutic effect on tumors such as breast cancer 7 , pancreatic cancer 8 , lung cancer 9 , ovarian cancer and prostate cancer 10 . It has been found that small doses of aspirin can reduce the risk of multiple cancers, and in vitro aspirin inhibits the growth of various cancer cells including breast cancer through COX-dependent and COX-independent pathway 11 .…”
Section: Introductionmentioning
confidence: 99%